CGD413 : User interface design / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2021)
User interface design is one of the elements in gaming whereby it affects the user experience thus enrich the gameplays. Techniques of user interfaces is taught to reinforce the understanding and development of game design as a whole.